PERANCANGAN IKLAN LAYANAN MASYARAKAT KESELAMATAN DI PERLINTASAN KERETA API DALAM MEDIA MOTION GRAPHIC - RAHMAT RAHMANDO, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Train become a transportation that liked by the society of Padang and surrounding areas. The timely departure and free from traffic jam are the advantages possessed by train, but the increasing cases of train accidents in West Sumatra especially in line of Padang-Pariaman becomes a very serious problem nowadays, almost every year there is an accident in railway crossing. These accidents occur mostly in railway tracks that do not have a doorstop, the government has not build a doorstep in every existing crossing because of constrained budget, therefore the society can not only rely on and wait for prevention efforts from the government.Based on these problems, the design of public service for the safety in railway crossings is created in motion graphic media. Motion graphic is chosen as the main media because it makes the object looked dynamic, interesting, and not boring. Motion graphic will be more effective as the main media, because it contains elements of video and audio, the message that is informed is easily understood.The purpose of this design is to make public service in motion graphic form that can remind the audience to care about the safety at the railway. In designing this motion graphic, 5W1H method (what, where, who, why, how) is used. Author analyzed public safety service advertisements at railway crossings as a study in designing motion graphic and supported by supporting media such as poster, sticker, key chain, pin, T-shirt, totebag and buff.Keywords: Padang West Sumatra, Safety at Railway Crossing, Motion Graphic